The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/aje/kwt441
|View full text |Cite
|
Sign up to set email alerts
|

Using Natural Language Processing to Improve Efficiency of Manual Chart Abstraction in Research: The Case of Breast Cancer Recurrence

Abstract: The increasing availability of electronic health records (EHRs) creates opportunities for automated extraction of information from clinical text. We hypothesized that natural language processing (NLP) could substantially reduce the burden of manual abstraction in studies examining outcomes, like cancer recurrence, that are documented in unstructured clinical text, such as progress notes, radiology reports, and pathology reports. We developed an NLP-based system using open-source software to process electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 34 publications
(38 reference statements)
1
106
0
Order By: Relevance
“…Recent studies have shown that NLP approaches can effectively extract meaningful information, such as adverse drug reactions, cancer staging, and disease progression from clinical notes. [55][56][57][58][59][60] Preliminary results suggest that NLP can identify documentation of advance care planning. 61 Several groups are currently working on using NLP or machine learning to identify and evaluate these discussions.…”
Section: Challenges and Lessons Learned From Ehr-based Metricsmentioning
confidence: 99%
“…Recent studies have shown that NLP approaches can effectively extract meaningful information, such as adverse drug reactions, cancer staging, and disease progression from clinical notes. [55][56][57][58][59][60] Preliminary results suggest that NLP can identify documentation of advance care planning. 61 Several groups are currently working on using NLP or machine learning to identify and evaluate these discussions.…”
Section: Challenges and Lessons Learned From Ehr-based Metricsmentioning
confidence: 99%
“…For example, if ambiguous terms such as "suggestive of" are mentioned and are accepted as favoring the diagnosis of a finding, an automated system's balance of sensitivity and specificity may be altered with a bias, whereas an expert may be able to consistently infer disposition from context (43). Ambiguity of abbreviations is another example.…”
Section: Resultsmentioning
confidence: 99%
“…This cascaded approach yielded a sensitivity and specificity of 80.6% and 91.6%, respectively, for overall status classification; 79.3% and 89.4%, respectively, for magnitude classification; and 68.6% and 85.9%, respectively, for certainty classification. Similarly, Carrell et al (43) used cTAKES to consolidate pathology and radiology reports plus clinical notes to detect cancer recurrence in women with early-stage invasive breast cancer. A custom-built dictionary with 1360 entries was created for pathologic findings.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Reuse of this unstructured data requires either manual abstraction, or automated information extraction approaches based on NLP [124]. Most information extraction efforts focused on phenotyping and chart abstraction improvement [125], research subjects recruitment and cohort identification for retrospective studies, and patient identification for improved treatment and follow-up. The extraction of phenotypes and other types of information include diseases and problems, investigations, treatments, combined in the 4th i2b2 NLP challenge [126], or medication details for example [127].…”
Section: F Extraction Of Information From Unstructured Clinical Datamentioning
confidence: 99%